2014
DOI: 10.5937/ffr1401047s
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of domestic Balkan donkey milk toward Listeria monocytogenes and Staphylococcus aureus

Abstract: The aim of this study was to investigate the antibacterial activity of raw milk from Domestic Balkan donkey breed toward Listeria monocytogenes and Staphylococcus aureus. Examination of antibacterial activity was performed in artificially contaminated milk samples by monitoring the changes of count of viable cells of tested bacteria during 8 hours of incubation at 38 °C. Lysozyme and fatty acids contents were also determined in donkey milk. The obtained results indicated inhibitory effect of donkey milk toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The mean lysozyme activity value was 217.04 ± 13.09 U/ml. Our results were in accordance with other studies carried out by ; Guo et al (2007); Pilla, Dapra, Zecconi, and Piccinini (2010); Sarić et al (2012); Sarić et al (2014); Vincenzetti et al (2011). The lysozyme content at 30 th day was significantly lower compared to the lysozyme content at 1 st and 15 th day of lactation (201.94 ± 10.96, 225.08 ± 7.05 and 224.11 ± 5.99 respectively, p<0.05).…”
Section: Lysozymesupporting
confidence: 93%
“…The mean lysozyme activity value was 217.04 ± 13.09 U/ml. Our results were in accordance with other studies carried out by ; Guo et al (2007); Pilla, Dapra, Zecconi, and Piccinini (2010); Sarić et al (2012); Sarić et al (2014); Vincenzetti et al (2011). The lysozyme content at 30 th day was significantly lower compared to the lysozyme content at 1 st and 15 th day of lactation (201.94 ± 10.96, 225.08 ± 7.05 and 224.11 ± 5.99 respectively, p<0.05).…”
Section: Lysozymesupporting
confidence: 93%
“…This suggests a long shelf life of donkey milk which could be stored longer with respect to raw cow milk [57]. In another study on the antimicrobial properties of donkey milk, Šarić and co-workers found a positive correlation between the high content of lysozyme and the antibacterial activity against Listeria monocytogenes and Staphylococcus aureus [58].…”
Section: Lysozymementioning
confidence: 93%
“…Several studies showed that DM has an anti-bacterial property against a wide range of pathogenic bacteria such as Escherichia coli, Salmonella enteritidis, Listeria monocytogène, Staphylococcus aureus, Bacillus cereus, Enterococcus faecalis, Shigella dysenteria, and against some yeasts [5]. The high content of lysozyme in DM is correlated with high anti-bacterial activity against Listeria monocytogenes and Staphylococcus aureus [8,[42][43][44][45], making DM safer, without food-borne pathogenic bacteria, and with a longer self-life. This anti-bacterial activity is due to its high value of anti-bacterial components [46][47][48], mainly some whey proteins such as lysozyme and lactoferrin [44,45] (Figure 1).…”
Section: Anti-microbial Activity Of Donkey Milkmentioning
confidence: 99%
“…Considering its functional properties and its nutritional values, DM becomes an attractive product for health, technology, cosmetic industry, and others. The health effects of DM consumption are mainly related to low allergenicity [3,5,67,68], anti-microbial activity [5,32,[42][43][44]57,69,70], regulation of iron homeostasis [5], anti-inflammatory and immune system modulation, innate immune system, immunosenescence [5,20,71,72], anti-hypertensive [5,[73][74][75], anti-diabetic [76], anti-tumoral [5,77,78], stimulate development [5,68], anti-stress and anti-oxidant activity [5,25,65,76], and anti-osteoporosis [5,68,79] (Figure 2). DM is supplied in different forms: liquid milk, fermented products (with higher peptide content and bioavailable calcium source), freeze dried, and spray dried powders [87].…”
Section: Food and Other Applications Of Donkey Milkmentioning
confidence: 99%